2013
DOI: 10.4161/cc.23719
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 overexpression perturbs DNA replication and induces replication-associated DNA double-strand breaks in acquired radioresistant cells

Abstract: Fractionated radiotherapy (RT) is widely used in cancer treatment, because it preserves normal tissues. However, repopulation of radioresistant tumors during fractionated RT limits the efficacy of RT. We recently demonstrated that a moderate level of long-term fractionated radiation confers acquired radioresistance to tumor cells, which is caused by DNA-PK/AKT/GSK3β-mediated cyclin D1 overexpression. The resulting cyclin D1 overexpression leads to forced progression of the cell cycle to S-phase, concomitant wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…3B-C), which is characteristic of global transcriptional activation (53). In addition, cycline D1 expression regulates G 1 -S phase progression (54), and expression levels of this protein are modulated by the chromatin-modeling factor SNF2H and the CCAAT-binding protein C/EBP (55). Our quantitative data FIG.…”
Section: Mass Spectrometric Identification and Quantification Of Thementioning
confidence: 67%
“…3B-C), which is characteristic of global transcriptional activation (53). In addition, cycline D1 expression regulates G 1 -S phase progression (54), and expression levels of this protein are modulated by the chromatin-modeling factor SNF2H and the CCAAT-binding protein C/EBP (55). Our quantitative data FIG.…”
Section: Mass Spectrometric Identification and Quantification Of Thementioning
confidence: 67%
“…12 Cell cycledependent proteolysis of cyclin D1 is essential for S-phase progression, and cyclin D1 accumulation during S phase perturbs DNA replication. 15,20 These perturbations in DNA replication, e.g., DNA re-replication and the suppression of replication-fork progression, lead to DSBs. 15,20 Here we observed that normal human fibroblasts exposed to long-term FR accumulated nuclear cyclin D1 and suffered chromosome damage in the form of micronuclei (Fig.…”
Section: Nuclear Accumulation Of Cyclin D1 Following Fr Exposurementioning
confidence: 99%
“…12 AKT is transiently activated after SR exposure 13,14 but constitutively activated in cells exposed to FR for >14 d. 7 These results suggest that exposure to FR affects the AKT signaling pathway. 7,15 Constitutive AKT activation following FR exposures downregulates the nuclear export and proteolysis of cyclin D1, which results in the nuclear retention of cyclin D1 during S phase. 7 We recently reported that the abnormal expression of cyclin D1 during S phase damages DNA by blocking DNA replication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular basis of radioresistance remains to be elucidated. The radioresistant phenotype has been correlated with characteristics such as the enhanced repair of IR-induced DNA damage [1] [2] [3] [4], overexpression of cyclin D1 [5] [6], higher rates of cell growth and migration [7], a lower concentration of reactive oxygen species (ROS) in cells [8] [9] [10], inactivation of apoptotic proteins [11] and alterations in radiation-induced autophagy [12] [13]. A disadvantage of studying radioresistance is the lack of adequate radioresistant models reflecting the clinical features of this phenomenon.…”
Section: Introductionmentioning
confidence: 99%